METHODOLOGICAL BASIS OF STANDARD GAMBLE METHOD USAGE IN QUALITY OF LIFE ASSESSMENT IN PHARMACOECONOMIC RESEARCHES - R. I. Yagudina; A. Ju. Kulikov; D. T. Ugrekhelidze (IRBIS LLC, 2015)
Utility assessment is one of the most important stages of pharmacoeconomic analysis. Most of utility researches are conducted using standard gamble method which is considered the classic instrument of health state utilities assessment. This article presents a methodology of conducting researches using standard gamble. The problems and features of the interpretation of the results are covered, examples of research using props, as well as computer programs that calculate the values of the utility automatically are described.